LoRa: A Proposed Connectivity Technology for Internet of Things Applications in the Kurdistan Region of Iraq - Sarko Salahadin Ahmad; Bakhtiar Ibrahim Saeed (Kurdistan Journal of Applied Research)
The Internet of Things (IoT) has become one of the most important trends of this century. Recent advances in many different communication technologies and protocols, and access to low-cost and low-power microcontrollers and sensors have made it more prevalent.